Upaya Peningkatan Pengetahuan Tentang Hipertensi pada Keluarga - Herni Oktriani; Iis Sukaesih; indah dwi; Julia Putri; lidia naelani (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2021)
Introduction: Hypertension is a disease that causes death and is a major risk factor for heart and blood vessel illness for stroke, congestive heart failure, heart attack, and kidney illness. The upgrade of hypertension cases is caused by a deficiency of knowing with the result that person do not understand how to prevent and treat it. Therefore, it is necessary to have health education to increase and increase knowledge about hypertension so that hypertensive patients can change their lifestyles. Objective: The goal of health education is to upgrade the participant's knowledge about the management and prevention of hypertension. Method: The method used in this health education is direct health education (offline) and discussion. Result: The evaluation results show that the activities have been carried out properly following the indicators and results criteria on the observation sheet instrument. The observation sheet is based on five dimensions, namely timeliness and duration, participation, knowledge, job description, and problem-solving. The evaluation sheet is filled out by independent observers. Conclusion: By the evaluation results, health education activities to increase knowledge have been successful with individuals with indicators of timeliness and duration, participation, knowledge, job descriptions, and problem-solving. In the discussion session, all participants were enthusiastic to ask questions and listen and understand what the presenters answered from what they asked. In the post-implementation evaluation session, participants answered what was asked without hesitation. Observation results showed an increase in participant's knowledge. The pre-implementation evaluation showed that one out of 3 people gave responses to the questions given, could answer the questions correctly, but after the heath education, all three participants gave the correct feedback. This shows a change in the status of knowledge before and before health education is carried out. suggestions for this activity need time management so that counseling can be carried out according to the time specified in the SAP.